Effects of short-form video app addiction on academic anxiety and academic engagement: The mediating role of mindfulness - Li, Gongyu; Geng, Yaxuan; Wu, Tingting (Frontiers in Psychology, 2024)
Introduction: The impact of short-form video app addiction on academic performance, including academic anxiety and engagement, has not been adequately explored or addressed. Method: This study tested the effects of short-form video app addiction on academic anxiety and academic engagement and the mediating role of mindfulness in these relationships. The participants were 1,879 undergraduates in China who completed the Short-Form Video App Addiction Scale, Mindful Attention Awareness Scale, Academic Anxiety Sub-questionnaire of Academic Emotions Questionnaire, and Engagement Scales. Structural equation modelling (SEM) was used to analyse the data. Results: The results indicate that short-form video app addiction has significant positive effects on academic anxiety and negative effects on academic engagement. Furthermore, short-form video app addiction has significant indirect effects on academic anxiety and engagement via mindfulness. The proportions of the mediation effects are 19.23% and 51.85%, respectively. Discussion: The implications and limitations of this study are discussed.